2013
DOI: 10.1089/vbz.2012.1118
|View full text |Cite
|
Sign up to set email alerts
|

Co-Infection with ‘CandidatusNeoehrlichia mikurensis’ andBorrelia afzeliiinIxodes ricinusTicks in Southern Sweden

Abstract: The tick-borne bacterium 'Candidatus Neoehrlichia mikurensis' has recently been recognized as a human pathogen in Europe and appears to be the second most common pathogenic bacterium in Ixodes ricinus ticks in central Europe, second to Borrelia afzelii. Here, we investigate the prevalence of 'Candidatus N. mikurensis' in host-seeking ticks in southern Sweden and the rate of co-infection with B. afzelii. We developed a real-time qPCR assay targeting the groEL gene of 'Candidatus N. mikurensis' and applied this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 27 publications
4
27
0
Order By: Relevance
“…Although the prevalence of other tick‐borne pathogens in Norway is known to vary from place to place (Kjelland et al, ; Paulsen et al, ; Soleng et al, ; Soleng & Kjelland, ; Tveten, , ), we are not aware of any study showing such a clear and sharply delineated area of reduced prevalence. Borrelia afzelii and N. mikurensis have been found co‐infecting ticks with a higher prevalence than is expected by random chance (Andersson, Bartkova, Lindestad, & Raberg, ; Andersson, Scherman, & Raberg, ; Kjelland et al, ). Because of this association, it would be particularly interesting to investigate whether B. afzelii shows a similar distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of other tick‐borne pathogens in Norway is known to vary from place to place (Kjelland et al, ; Paulsen et al, ; Soleng et al, ; Soleng & Kjelland, ; Tveten, , ), we are not aware of any study showing such a clear and sharply delineated area of reduced prevalence. Borrelia afzelii and N. mikurensis have been found co‐infecting ticks with a higher prevalence than is expected by random chance (Andersson, Bartkova, Lindestad, & Raberg, ; Andersson, Scherman, & Raberg, ; Kjelland et al, ). Because of this association, it would be particularly interesting to investigate whether B. afzelii shows a similar distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Neoehrlichia mikurensis" since the prevalence of B. afzelii in ticks is about twice as high as that of "Ca. Neoehrlichia mikurensis" (5,19). This suggests that the efficiency of transmission from tick to vole might be higher for "Ca.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas one study showed that nymphs were twice as likely to be infected by C. Neoehrlichia mikurensis as were adult ticks [28], the opposite pattern was seen in another study [31], and no difference in rates of infection between the life stages was observed in a third study [49]. C. Neoehrlichia mikurensis-infected ticks have been collected from birds and a variety of mammals (Table 1), all of which may facilitate the spread of the infection in the environment.…”
Section: Vectors Reservoirs and Transmissionmentioning
confidence: 99%
“…C. Neoehrlichia mikurensis-infected ticks may be co-infected with other pathogenic species, such as Borrelia, Babesia, Rickettsia, and Anaplasma [14,26,28,31,44,49,56]. The rate of co-infection of ticks with C. Neoehrlichia mikurensis and Borrelia species is higher than predicted, and it may be more common for C. Neoehrlichia mikurensis to occur together with Borrelia than to appear alone in ticks [28,49,55]. This is probably a consequence of the feeding of ticks on rodents that are infected with both pathogens.…”
Section: The Agentmentioning
confidence: 99%